Characterization of rabbit hepatitis E virus isolated from a feral rabbit - Mendoza, Milagros Virhuez; Yonemitsu, Kenzo; Ishijima, Keita; Minami, Shohei; Supriyono; Tran, Ngo T.B.; Kuroda, Yudai; Tatemoto, Kango; Inoue, Yusuke; Okada, Ai; Shimoda, Hiroshi; Kuwata, Ryusei; et al. (Veterinary microbiology, 2021)
•Rabbit hepatitis E virus (HEV) circulates among feral rabbits in Japan.•Persistent HEV infection was observed in a rabbit experimentally infected with the HEV isolate JP-59.•Further studies are required to determine the zoonotic risk of rabbit HEV. Rabbit hepatitis E virus (HEV) has been detected among rabbits and recently isolated from immunocompromised patients, suggesting zoonotic transmission. In this study, HEV infection among feral rabbits (Oryctolagus cuniculus) was assessed by detection of anti-HEV antibodies and HEV RNA. The prevalence of anti-HEV antibodies in sera was of 33 % (20/60) and HEV RNA was detected from only one of fecal swabs (1.7 %, 1/58). Furthermore, one naïve rabbit was intravenously inoculated with the suspension of the HEV-positive fecal specimen, exhibiting persistent HEV shedding in feces, intermittent viremia, seroconversion to anti-HEV IgM and IgG, and high alanine aminotransferase (ALT) values, indicating persistent HEV infection. The isolate JP-59 had a length of 7,282 bp excluding a poly (A) tail and possessed the characteristic 93 bp-insertion in ORF1. Phylogenetic analysis indicated that JP-59 formed a cluster with other rabbit HEV isolates from rabbits and human origin. The JP-59 shared the nucleotide sequence identities less than 87 % with other rabbit HEVs, suggesting that a novel rabbit HEV strain was circulating in Japan.